Inscuteable mRNA localization is dynein-dependent and regulates apicobasal polarity and spindle length in Drosophila neuroblasts. - Hughes, J.R.; Bullock, S.L.; Ish-Horowicz, D. (Current Biology, 2004)
Drosophila neuroblasts undergo asymmetric divisions along the apicobasal axis to produce two daughter cells of unequal size and different developmental fate. Inscuteable (Insc) protein functions as part of an apically localized complex to coordinate orientation of the mitotic spindle and basal sorting of cell fate determinants. insc mRNA transcripts also localize apically in neuroblasts, yet the mechanism underpinning this process and its developmental significance are unknown. Here, we show that the Egalitarian (Egl)/Bicaudal-D (BicD)/dynein mRNA transport machinery mediates apical localization of insc mRNA transcripts in neuroblasts, and we provide evidence that insc localization is required for efficient apical targeting of Insc protein. egl and BicD mutant neuroblasts display defects in apicobasal polarity, which is consistent with apical Insc activity being reduced. Also, we observe shortened mitotic spindles at metaphase in egl, BicD, and insc mutant neuroblasts and demonstrate a previously unknown, dose-dependent requirement for Insc in augmenting metaphase spindle length. We conclude that localization of insc mRNA transcripts in neuroblasts confers maximal levels of apical Insc activity, which is required for accurate control of metaphase spindle length, division orientation, and asymmetric cell division.